Teknologi Informasi dan Kinerja Perguruan Tinggi - Hayati, Patma; Luthfi Fadhilah Syarthony, Adib; Nabila, Salsa; Novita Syahfitri, Anisa; Widya Pradana, Deby (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is to conduct a literature review of previous research on Information Technology and Higher Education Performance from 2020 - 2024. Information Technology Systems as a tool to help the performance of higher education, which is widely used in universities to improve their organization. this study uses SLR which presents quantitative data on Information Technology and Higher Education Performance there are measurements used, namely journals, variables, and theories as well as the field of science reaserch approach. The study results showed 30 articles from accredited national journals and national journals. The topic of higher education performance is influenced by information technology variables, quality assurance, learning perspectives, growth, internal perspectives. The theory used is the information technology system in higher education performance. State universities and private universities are researching a lot about Information Technology. But only a few universities use widely used Information Technology Systems such as Academic Management Information Systems, Sevima Platform, and E-Learning. Although universities have successfully implemented information technology systems, the main challenges faced are the digital divide, access to technology, and security. This research provides insights, benefits, and constraints in implementing and recommending Information Technology Systems and College Performance.